Determining Immune and miRNA Biomarkers Related to Respiratory Syncytial Virus (RSV) Vaccine Types - Atherton, Lydia J.; Jorquera, Patricia A.; Bakre, Abhijeet A.; Tripp, Ralph A. (Frontiers in Immunology, 2019)
Respiratory Syncytial Virus (RSV) causes serious respiratory tract illness and substantial morbidity and some mortality in populations at the extremes of age, i.e., infants, young children, and the elderly. To date, RSV vaccine development has been unsuccessful, a feature linked to the lack of biomarkers available to assess the safety and efficacy of RSV vaccine candidates. We examined microRNAs (miR) as potential biomarkers for different types of RSV vaccine candidates. In this study, mice were vaccinated with a live attenuated RSV candidate that lacks the small hydrophobic (SH) and attachment (G) proteins (CP52), an RSV G protein microparticle (GA2-MP) vaccine, a formalin-inactivated RSV (FI-RSV) vaccine or were mock-treated. Several immunological endpoints and miR expression profiles were determined in mouse serum and bronchoalveolar lavage (BAL) following vaccine priming, boost, and RSV challenge. We identified miRs that were linked with immunological parameters of disease and protection. We show that miRs are potential biomarkers providing valuable insights for vaccine development.